2011
DOI: 10.1186/1471-2261-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary assessment of tako tsubo cardiomyopathy: a prospective case study

Abstract: BackgroundThe cause of tako tsubo cardiomyopathy remains unclear. We used a multidisciplinary approach to investigate if a common pathophysiological denominator could be outlined.MethodsWithin 3 days following symptom presentation and again after 3 months we investigated all patients coming to our institution and diagnosed with tako-tsubo cardiomyopathy. Patients underwent extensive biochemical screening. Left ventricular function was evaluated by echocardiography and contrast-enhanced cardiac magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Waldenborg et al, in a prospective cohort study with systematic screening by psychiatric interview, did not find abnormal prevalence of major depressive disorder in a group of 13 patients with TTC. 15 Del Pace et al, in a recent prospective case-control study, found that high anxiety is a common trait in patients with TTC but is not more frequent than in those with acute myocardial infarction. 16 These results are surprising because several previous retrospective studies based on past psychiatric history and use of antidepressant medication suggested an increased prevalence of ADD in patients with TTC.…”
Section: Discussionmentioning
confidence: 99%
“…Waldenborg et al, in a prospective cohort study with systematic screening by psychiatric interview, did not find abnormal prevalence of major depressive disorder in a group of 13 patients with TTC. 15 Del Pace et al, in a recent prospective case-control study, found that high anxiety is a common trait in patients with TTC but is not more frequent than in those with acute myocardial infarction. 16 These results are surprising because several previous retrospective studies based on past psychiatric history and use of antidepressant medication suggested an increased prevalence of ADD in patients with TTC.…”
Section: Discussionmentioning
confidence: 99%
“…In another condition triggered by severe emotional or physical stress called Takotsubo cardiomyopathy, patients present with depressed left ventricular function, elevated troponin levels, and angiographically normal coronary arteries (24). HRV in this condition has been assessed by several groups who both found that HRV was depressed during the acute setting, but significantly increased after recovery (25, 26). Results of these studies suggest that HRV is a marker of autonomic dysregulation that occurs as a result of severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…The psycho-somatic connections underlying TTC are far from clear [ 14 , 15 , 39 ]. In a case study published recently in this journal, Waldenborg et al even proposed to avoid terms as “stress-induced cardiomyopathy” or “broken heart syndrome” for TTC [ 49 ]. They detected symptoms of acute posttraumatic stress in 9 out of 13 (69%) TTC patients (2 patients qualified for having PTSD) and similar numbers of acute distress can be found in patients with acute myocardial infarction [ 49 ].…”
Section: Discussionmentioning
confidence: 99%